Pharmacological Differences Between Static and Dynamic Allodynia in Mice With Herpetic or Postherpetic Pain - Atsushi Sasaki; Kenichi Serizawa; Tsugunobu Andoh; Kimiyasu Shiraki; Hiroki Takahata; Yasushi Kuraishi (Elsevier, 2008)
In the present study, we investigated whether dynamic and static allodynia would be developed in the affected dermatome in murine models of herpetic pain and postherpetic neuralgia and pharmacologically characterized the allodynia. Inoculation with herpes simplex virus type-1 on the femur induced skin lesions in the dermatome including the plantar region of the hind paw from day 5 to day 21 after inoculation. Dynamic allodynia became apparent in the hind paw from day 3 to at least day 42. Static allodynia was not obvious during the stage of herpetic pain and gradually increased after the lesion healing. Mexiletine hydrochloride (30 mg/kg, p.o.) and ketamine hydrochloride (50 mg/kg, i.p.) produced a moderate attenuation of static but not dynamic allodynia. Diclofenac sodium (50 mg/kg, i.p.) did not affect both static and dynamic allodynia. Gabapentin (30 mg/kg, p.o.) markedly inhibited both static and dynamic allodynia. Developmental and pharmacological differences between static and dynamic allodynia suggest that independent mechanisms are responsible for dynamic and static allodynia. This murine model may be useful for the study of the mechanisms of dynamic allodynia of herpetic pain or postherpetic neuralgia and the development of new analgesics effective against the dynamic allodynia. Keywords:: dynamic and static allodynia, herpes simplex virus type-1, herpetic pain, postherpetic neuralgia, dorsal root ganglion